Peer Bullying in the Preadolescent Stage: Frequency and Types of Bullying and the Affecting Factors - Zehra Çalışkan; Derya Evgin; Meral Bayat; Nuray Caner; Bahriye Kaplan; Ahmet Öztürk; Dilara Keklik (Galenos Yayinevi, 2019)
Aim:This study was conducted to determine the types, frequencies and the affecting factors of peer bullying among 6th, 7th, and 8th grade students of secondary schools in a city center in Cappadocia.Materials and Methods:A total of 3.059 students were attending secondary schools in a city center and this study sample consists of 1.288 students. Prior to the study, approval from the ethical council and institute, as well as written consent from students and their families were obtained. Data were collected via individual information forms and the Traditional Peer Bullying scale by the researcher through face-to-face interviews and the data obtained were evaluated by chi-square, single, and multiple logistic regression analysis.Results:It was determined that the mean age of the students was 12.81±0.93 years, of them 51.7% were girls, 12.0% did bullying, 15.9% were exposed to bullying, 52.1% were exposed to verbal bullying, and 13.4% were exposed to physical bullying. Multiple logistic regression revealed that the most important factors affecting the bullying of other students were family structure, attitude towards school, and gender; those factors affecting exposure to bullying were attitude toward school, body mass index, and economical status. As the age of the students increased by one year, the likelihood of bullying increased by 1.2 times. Boys were bullied 1.5 times more than girls, and the students of separated parents were bullied 2.7 times more than those whose parents stayed together (p<0.05).Conclusion:As bullying within schools is an important problem, it may be advisable to take into account the factors affecting bullying (age, gender, economic situation, family structure, attitude toward school, etc.) when conducting studies to prevent bullying in schools.